2018
DOI: 10.1093/inthealth/ihy015
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of exclusive breastfeeding across three time points in Bangladesh: an examination of the 2007, 2011 and 2014 Demographic and Health Survey

Abstract: EBF prevalence in Bangladesh increased between 2007 and 2011 and then decreased between 2011 and 2014. The increase in 2011 may have been the result of widespread initiatives to promote EBF in that time frame. Due to the unexplained decrease in EBF between 2011 and 2014, there is still a need for interventions such as peer counselling, antenatal education and community awareness to promote EBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Higher parity may translate to experience in child rearing and thus, awareness of what is required in terms of EBF [35]. In contrast, a study in Bangladesh reported no significant association between parity and EBF [38].…”
Section: Discussionmentioning
confidence: 99%
“…Higher parity may translate to experience in child rearing and thus, awareness of what is required in terms of EBF [35]. In contrast, a study in Bangladesh reported no significant association between parity and EBF [38].…”
Section: Discussionmentioning
confidence: 99%
“…The decline in the EBF rate in Bangladesh may have happened due to discontinuance of activities to promote EBF practices which took place in around 2011 [ 16 ]. Lack of paternal and family support, workplace barriers [ 2 , 17 ] such as shorter maternity leave [ 17 ], breastfeeding in unfriendly work environments (as most offices do not have daycare centers and do not allow time and/or space for expressing breastmilk) and long working hours [ 16 ] etc. also may lower the rate.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of mothers practicing exclusive breastfeeding in Bangladesh has increased from 42.5% in 2007 to 65.0% in 2011 as a result of widespread initiatives to promote exclusive breastfeeding. However, the exclusive breastfeeding rate in Bangladesh has gradually declined to 55.0% in 2018 [5,11]. Reasons for that drop include the increase in formula feeding rates, the misperception that powdered milk is better than breast milk, a lack of knowledge about the harmful effects of milk powder, as well as sociocultural factors and a lack of appropriate breastfeeding practices [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for that drop include the increase in formula feeding rates, the misperception that powdered milk is better than breast milk, a lack of knowledge about the harmful effects of milk powder, as well as sociocultural factors and a lack of appropriate breastfeeding practices [12,13]. Practice-related factors for breastfeeding included region, delivery type, job, access to mass media, breastfeeding counseling, and antenatal and postnatal care [11,14]. Thus, interventions for improving community awareness of breastfeeding benefits and its importance should be developed, and it is necessary to provide prenatal education related to proper breastfeeding practices.…”
Section: Introductionmentioning
confidence: 99%